PENGARUH EFEK LEVERAGE SEBAGAI PEMODERASI TERHADAP HUBUNGAN ANTARA RETURN ON EQUITY (ROE) DAN STRUKTUR MODAL - Sherly Fristylia Ramdini; Francis Hutabarat (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
Research that can be done to study the relationship of return on equity to capital structure with Leverage dieminten period 2017-2018 Property Real Estate Subsector on the IDX. Secondary data retrieval is based on 14 units from the Property Real Estate sub-sector using Purposive Sampling techniques and related annual reports with the following company codes APLN, ASRI, KIJA, GAMA, BSDE, BKSL, CTRA, MYRX, SMDM, SMRA, LPCK, LPKR, BEST, and FATHER. The results of this study indicate that leverage has a good or positive relationship with the capital structure in the Real Estate and Property emintent for the period 2017-2018. While ROE does not have a relationship related to the Capital Structure of the emintent in Real Estate and Property listed on the IDX for the period 2017-2018